Design and simulation of an on-chip oversampling converter with a CMOS-MEMS differential capacitive sensor - Ma, Li Ya; Nordin, Anis Nurashikin; Khan, Sheroz (2011)
This paper presents the design and analysis of an integrated oversampling converter with MEMS capacitive sensor. The MEMS capacitive sensor is a comb-drive which provides change in capacitance when change in acceleration is detected. The analog-to-digital converter (ADC) is a first-order 1-bit sigma-delta (Σ-Δ) converter. Σ-Δ ADCs are suitable for MEMS sensors since their output voltage are in mV and are low frequencies. Both the Σ-Δ ADC and MEMS capacitive sensor were designed in Silterra’s 0.13μm CMOS process. Simulation of the Σ-Δ ADC was conducted using CadenceTM Spectre, while the MEMS sensor was simulated by COMSOL Multiphysics®. Results indicate that the Σ-Δ ADC can process small voltage output of the MEMS sensor and convert it into digital signals satisfactorily.